A Linguistic and Literary Analysis of the Term "Āzar" in the Qurʾān - Seyyed Mahmoud Tayyeb Hosseini; Sepideh Moqimi (آموزه‌های قرآنی)
Among the Qurʾānic terms associated with the Prophet Abraham (Ibrāhīm), the word "Āzar" holds particular significance. This term appears only once in the Qurʾān, in Sūrat al-An‘ām (6:74): "And when Abraham said to his father Āzar, ‘Do you take idols for deities?’" Lexicographers and exegetes have proposed diverse perspectives regarding the nature and meaning of Āzar. From a comprehensive standpoint, these perspectives can be examined from two fundamental aspects: its ontological status and its semantic implications. This study employs a descriptive-analytical method with a linguistic approach, drawing upon library-based research to elucidate the concept and function of this term in the Qurʾānic discourse. The research findings reveal multiple interpretations of Āzar: as a name for an idol; as a descriptive term denoting diligence and industriousness; as a word expressing reproof and prohibition of falsehood; as the name of Abraham’s servant; and as the father of Abraham during his period of polytheism, referred to as Ab. However, within Islamic tradition and post-Qurʾānic scholarship, Āzar has predominantly been perceived as the name of a polytheist and idolater, whom the Qurʾān designates as Ab (father) of Abraham. According to the predominant Shi‘a view, Āzar was either Abraham’s paternal uncle or his maternal grandfather. Conversely, the majority of Sunni scholars regard him as Abraham’s biological father. Nevertheless, several critical factors-such as the absence of Āzar’s name or title as Abraham’s father in the Biblical and historical sources, as well as the Qurʾānic distinction between "wālid" (Arabic: والد, lit: biological father) and "Ab" (Arabic: أب, lit: paternal figure)-support the conclusion that Āzar was not the actual biological father of Abraham.